2000
DOI: 10.1034/j.1600-0722.2000.108003247.x
|View full text |Cite
|
Sign up to set email alerts
|

Calcium leaching from dentin and shear bond strength after etching with phosphoric acid of different concentrations

Abstract: Based on the H2O-P2O5-CaO phase diagram, we hypothesize that a phosphoric acid concentration around 27 wt% leaches most calcium from dentin. We also hypothesize that bond strength is affected by resin infiltration, and that resin infiltration becomes incomplete when calcium leakage exceeds a certain value. Dentin disks were cut from human molars. Eight phosphoric acid concentrations were prepared (15.7-51.2 wt%). For each acid group, there were four etch time subgroups (15, 30, 60 and 120 s). The dentin disks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 5 publications
0
1
0
3
Order By: Relevance
“…2 During dentin acid-etching, the mineral content of the dentin surface is removed, and the collagen fibrils remain supported by water. 3 The moist bonding technique prevents the collagen fibers from collapsing and provides stability to the collagen, thus enabling greater infiltration of adhesive monomers. 4 However, some studies have found that the resin monomer infiltration may be incomplete even when the "wet" bonding technique is used, 5 suggesting that another factor affect hybridization, the composition of adhesive systems.…”
Section: Introductionmentioning
confidence: 99%
“…2 During dentin acid-etching, the mineral content of the dentin surface is removed, and the collagen fibrils remain supported by water. 3 The moist bonding technique prevents the collagen fibers from collapsing and provides stability to the collagen, thus enabling greater infiltration of adhesive monomers. 4 However, some studies have found that the resin monomer infiltration may be incomplete even when the "wet" bonding technique is used, 5 suggesting that another factor affect hybridization, the composition of adhesive systems.…”
Section: Introductionmentioning
confidence: 99%
“…Bu duruma asit uygulanan gruplarda kullanılan %35'lik fosforik asitin hidroksiapatit kristallerini ve dolayısı ile kalsiyumu ortamdan uzaklaştırarak, kimyasal bağlantıyı ortadan kaldırması veya azaltması neden olmuş olabilir. Yapılan çalışmalarda yüksek bağlanma değeri göste-ren örneklerin koheziv ve karışık tip başarısızlık gösterir-ken, düşük bağlanma değerlerine sahip örneklerin daha çok adeziv başarısızlık gösterdiği rapor edilmiştir (40)(41)(42). Bu çalışmada da örneklerin çoğunda karışık veya koheziv tip başarısızlık gözlenmiştir (Resim 2).…”
Section: Bulgularunclassified
“…Na superfície que recebeu o tratamento com o ácido fosfórico a 35%, por 15 segundos, pode-se observar a presença de túbulos dentinários totalmente desobliterados, remoção completa da "smear layer" com ausência de "smear plugs" e dentina peritubular e intratubular bem definidas. Essas características morfológicas também foram observadas nos trabalhos de JACOBSEN et al 51 , em 2000, TEBECHRANI;…”
Section: Nas Superfícies Onde Foram Aplicados Os Sistemas Adesivos Prunclassified